The Pregnant and Lactating Mothers KAP (Knowledge, Attitude and Practice) and Nutritional Care during Antenatal and Postnatal Period in Ukhia, Coxs Bazar, Bangladesh - Hasan, M. N.; Khan, M. N. I.; Sultan, M. Z. (Journal of Scientific Research, 2016)
The nutritional status of women before, during and after pregnancy contributes a good deal to their own health and, to the health of their children and other family members. In Bangladesh, there is enormous amount of mother and child death and morbidity related to inadequate nutrition, socioeconomic condition, education level, hygienic condition and various care practices. The study was conducted to see the nutritional KAP (knowledge, attitude and practice) during antenatal and postnatal care of the pregnant and lactating mother in Ukhia Upazilla of Coxs Bazar in Bangladesh among 337 pregnant and lactating mothers who had at least one child aged less than five years old by random sampling in 2010.The antenatal and postnatal care services availability was observed unsatisfactory. The study revealed that the nutritional lacking was not only poverty stricken, but also their poor knowledge, attitude and practice on health, hygiene, reproductive health, antenatal care, post natal care and nutritious food.